Antifungal Susceptibility Profiles of Olorofim (Formerly F901318) and Currently Available Systemic Antifungals against Mold and Yeast Phases of Talaromyces marneffei - Zhang, Jing (Antimicrob Agents Chemother, 2021)
In vitro antifungal susceptibility profiling of 32 clinical and environmental Talaromyces marneffei isolates recovered from southern China was performed against olorofim and 7 other systemic antifungals, including amphotericin B, 5-flucytosine, posaconazole, voriconazole, caspofungin, and terbinafine, using CLSI methodology. In comparison, olorofim was the most active antifungal agent against both mold and yeast phases of all tested Talaromyces marneffei isolates, exhibiting an MIC range, MIC(50), and MIC(90) of 0.0005 to 0.002 μg/ml, 0.0005 μg/ml, and 0.0005 μg/ml, respectively.